Analisis Persepsi Tentang Brevet Pajak dan Pertimbangan Pasar Kerja Terhadap Minat Karir di Bidang Perpajakan (Studi Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang dan Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang) - Kurniawan, Tio Candra; Amin, Moh.; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Tax brevet training needs to be held to hone skills and add expertise to graduates of accounting degrees. Tax brevet training is an important component for accounting graduates who are interested in working in the field of taxation. Consideration of the labor market is something that must be done because this relates to the job to be chosen in the future. Careers in the field of taxation are less desirable so that accounting students have great opportunities. Profession in the field of taxation is needed so that taxation in Indonesia can run well. The lack of interest of accounting students for a career in the field of taxation is due to the lack of knowledge and expertise of students in the field of taxation.Keyword: Tax brevet, labor market considerations, interest in a career in taxation